Demo eines Intelligenten Diagramm Assistenten (IDIAS) - Thies, S.; Gutkauf, B.; Domik, Gitta (Proceedings 5. GI Workshop Adaptivität und Benutzermodellierung in interaktiven Softwaresystemen)

User Adaptive Presentation of Information - Gutkauf, B.; Thies, S.; Domik, Gitta (Proceedings 2nd International Symposium on Global Engineering Networking)

Glenk, Hartmut: Die eingetragene Genossenschaft, in Schriftenreihe: Praxis des Handels- und Wirtschaftsrechts Heft 7; Beck 1996 - Krimphove, Dieter (Deutsche Notar-Zeitschrift)

Rademacher, Ulf: Der Europäische Betriebsrat. Die Richtlinie 94 / 45 / EG des Rates vom 22. 4. 1994 und ihre Umsetzung in nationales Recht; Nomos: Universitätsschriften Recht 1997 - Krimphove, Dieter (Recht der Arbeit (RdA))

Eva M. K. Häußling: Soziale Grundrechte in der portugiesi-schen Verfassung von 1976; in: Beiträge zum ausländischen und vergleichenden öffentlichen Recht Bd. 10, Diss. Bonn 1996; Nomos-Verlagsgesellschaft, Baden-Baden 1997 - Krimphove, Dieter (Euro A S)

A subdivision algorithm for the computation of unstable manifolds and global attractors - Dellnitz, Michael; Hohmann, Andreas (Numerische Mathematik)

Europäisches Wirtschaftsrecht - Krimphove, Dieter; Schollmeier, Andres (Bleckmann, Europarecht)

Der Gutgläubige Erwerb von Fahrnis in den Rechtsordnungen Europas -Ein Beitrag zur Rechtsvergleichung und Europäischen Rechtsharmonisierung unter Beachtung der Grundsätze der ökonomischen Analyse des "Europäischen Sachenrechts"- - Krimphove, Dieter (Festschrift für Axel Hunscha)

A Computer Architecture to Support Qualitative Simulation in Industrial Applications - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (e & i Elektrotechnik und Informationstechnik)

Parallel qualitative simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (Simulation Practice and Theory)

Signal Representations for Hidden Markov Model Based On-Line Handwriting Recognition - Dolfing, J.G.A.; Haeb-Umbach, Reinhold (ICASSP, Munich)
Addresses the problem of online, writer-independent, unconstrained handwriting recognition. Based on hidden Markov models (HMM), which are successfully employed in speech recognition tasks, we focus on representations which address scalability, recognition performance and compactness. 'Delayed' features are introduced which integrate more global, handwriting specific knowledge into the HMM representation. These features lead to larger error-rate reduction than 'delta' features which are known from speech recognition and even require fewer additional components. Scalability is addressed with a size-independent representation. Compactness is achieved with linear discriminant analysis. The representations are discussed and the results for a mixed-style word recognition task with vocabularies of 200 (up to 99% correct words) and 20000 words (up to 88.8% correct words) are given.

The development of a command-based speech interface for a telephone answering machine - Gamm, Stephan; Haeb-Umbach, Reinhold; Langmann, Detlev (Speech Communication)
This paper reports the design of a command-based speech interface for an answering machine or a voice mail system. Automatic speech recognition was integrated in order to facilitate the remote control and the retrieval of voice messages from any telephone in a speech-only dialogue. The design goal was that consumers would perceive the speech interface as a benefit compared with the common touch-tone interface. In this paper we will first describe the speech technology underlying the system. Then it will be shown how, based on this technology, the user interface was designed in a top-down approach. We started with the development of a concept and tested it by means of a Wizard-of-Oz simulation. After refining the concept in parallel design, it was implemented in a high-fidelity prototype. By means of qualitative user testing the design was improved in three iteration steps. The achievement of the design goal was finally verified with user tests in two countries.

Robust Speech Recognition for Wireless Networks and Mobile Telephony - Haeb-Umbach, Reinhold (Eurospeech)
The increased popularity of mobile telephony introduces both challenges and opportunitites for automatic speech recognition. ASR offers ways to simplify the use of mobile phones, notably in hands- and eyes-busy situations. However, the acoustic environment can be severely degraded and the wireless network may add additional distortions to the speech signal. This paper gives an overview of the sources of degradation and attempts to robust speech recognition for mobile communications. Emphasis is placed on approaches which are suitable for implementation in mobile terminals. Two example applications are described which illustrate the robustness issues and design considerations typical of low-cost noisy speech recognition: voice-dialling in a GSM phone and hands-free digit recognition in the car.

European Speech Databases for Telephone Applications - Hoege, H.; Tropf, H. S.; Winsky, R.; van den Heuvel, H.; Haeb-Umbach, Reinhold; Choukri, K. (ICASSP, Munich)
The SpeechDat project aims to produce speech databases for all official languages of the European Union and some major dialectal variants and minority languages resulting in 28 speech databases. They will be recorded over fixed and mobile telephone networks. This will provide a realistic basis for training and assessment of both isolated and continuous-speech utterances, employing whole-word or subword approaches, and thus can be used for developing voice driven teleservices including speaker verification. The specification of the databases has been developed jointly, and is essentially the same for each language to facilitate dissemination and use. There will be a controlled variation among the speakers concerning sex, age, dialect, environment of call, etc. The validation of all databases will be carried out centrally. The SpeechDat databases will be transferred to ELRA for distribution. The next databases to be recorded will cover East European languages.

Acoustic Front Ends for Speaker-Independent Digit Recognition in Car Environments - Langmann, Detlev; Fischer, Alexander; Wuppermann, Friedhelm; Haeb-Umbach, Reinhold; Eisele, Thomas (Eurospeech)
This paper describes speaker-independent speech recognition experiments concerning acoustic front end processing on a speech database that was recorded in 3 different cars. We investigate different feature analysis approaches (mel-filter bank, mel-cepstrum, perceptually linear predictive coding) and present results with noise compensation techniques based on spectral subtraction. Although the methods employed lead to considerable error rate reduction the error analysis shows that low signal-to-noise ratios are still a problem

Investigation of Acoustic Front Ends for Speaker-Independent Speech Recognition in the Car - Langmann, Detlev; Wuppermann, Friedhelm; Haeb-Umbach, Reinhold; Fischer, A.; Eisele, Thomas (Aachener Kolloquium on Signal Theory)

Hierarchical propagation of uncertain constraints - Hüllermeier, Eyke (in Proceedings EUFIT-97 5th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Approximation of fuzzy functions - Hüllermeier, Eyke (in Proceedings 4.Internationaler Workshop Fuzzy-Neuro-Systeme. Soest Germany)

Modellierung und Simulation unsicherer dynamischer Systeme und Anwendungen in der Diagnose - Hüllermeier, Eyke (In Proceedings ASIM Fachgruppentagung Soft Computing)

A user-adaptive chart editing system based on user modeling and critiquing - Gutkauf, Bernd; Thies, Stefanie; Domik, Gitta (User Modeling)